Factors Affecting The Primigravida Anxiety During The 3rd Trimester of Pregnancy Regarding The Upcoming Labor - Farida Aryani (Alma Ata University Press, 2018)
Pregnant women who experience anxiety experience an emotional reaction associated with the mother's concerns with the well-being of her self and her fetus, the sustainability of pregnancy, childbirth and when it plays a mother. This study aims to determine the factors affecting the primigravida anxiety of the 3rd trimester. The type of the research was quantitative with analytic observational method and with cross sectional design. The results show that the factors related to primigravic anxiety of third trimester were physical exercise in the form of pregnancy exercise with p value 0,000 (p <0,05), while maternal age, occupation, education level, and husband support had no effect on primagravida anxiety of the 3rd trimester where p value> 0.05. Conclusion: the factors associated with primigravida anxiety of the 3rd semester is a physical exercise in the form of pregnancy exercise